Membangun Kesadaran Digital: Edukasi Hoaks dan Disinformasi dengan Pendekatan Teknologi bagi Siswa SMKN 2 Jombang - Mu minin, Mu minin; Maisaroh, Siti (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
The rapid development of digital technology has significantly impacted the pattern of information dissemination, including among students. At SMKN 2 Jombang, the low level of digital literacy among students makes them vulnerable to hoaxes and disinformation circulating on social media. A lack of understanding of information verification and the absence of formal education on identifying hoaxes are key challenges in fostering digital awareness. To address this issue, the program "Building Digital Awareness: Hoax and Disinformation Education through a Technological Approach for SMKN 2 Jombang Students" was designed. This program adopts a participatory and technology-based approach using blended learning methods, encompassing digital literacy training, technology utilization workshops, the creation of educational content, and ongoing monitoring and evaluation. Through interactive training, hoax case simulations, and the use of digital tools such as fact-checking platforms and AI-powered fake news detectors, students are trained to recognize, analyze, and counter hoaxes. The outcomes of this program indicate an increased understanding and awareness among students of the importance of digital literacy, as well as improved critical thinking skills in evaluating information. Furthermore, the program supports the integration of digital literacy into school learning activities to promote sustainable and effective digital education.